Crystal Plasticity Modeling of Creep in Alloys with Lamellar Microstructures at the Example of Fully Lamellar TiAl - Schnabel, Jan E.; Scheider, Ingo (Frontiers in Materials, 2021)
A crystal plasticity model of the creep behavior of alloys with lamellar microstructures is presented. The model is based on the additive decomposition of the plastic strain into a part that describes the instantaneous (i.e., high strain rate) plastic response due to loading above the yield point, and a part that captures the viscoplastic deformation at elevated temperatures. In order to reproduce the transition from the primary to the secondary creep stage in a physically meaningful way, the competition between work hardening and recovery is modeled in terms of the evolving dislocation density. The evolution model for the dislocation density is designed to account for the significantly different free path lengths of slip systems in lamellar microstructures depending on their orientation with respect to the lamella interface. The established model is applied to reproduce and critically discuss experimental findings on the creep behavior of polysynthetically twinned TiAl crystals. Although the presented crystal plasticity model is designed with the creep behavior of fully lamellar TiAl in mind, it is by no means limited to these specific alloys. The constitutive model and many of the discussed assumptions also apply to the creep behavior of other crystalline materials with lamellar microstructures.